Dead firms causes and effects of cross-border corporate insolvency - Torres, Miguel M.; Cathro, Virginia; Gonzalez-Perez, Maria Alejandra (Emerald, 2016)
Why do firms die? This volume seeks to explore international and cross-disciplinary perspectives, if you like a forensic examination, autopsy or post mortem of how and why companies die. This alternate perspectives flips the focus on survival, as all existing firms are in truth survivors, to consider through the metaphors of death, (with forensic analysis, autopsy, post mortems and crime scene investigations) the lessons dead firms might offer. This book will contribute to the understanding of the development, antecedents, processes and consequences of corporate insolvency around the world. In general lines, insolvency is a state in which the debtor is proven unable to pay corporate debtors. We aim to explore the contemporary causes and effects of corporate cross-border insolvency (CCBI). In the realms of international business, CCBI could be mediated by events experienced during the internationalization of the firm, which may encompass a loss of capital, loss of revenue and loss of credit.
Keywords: Business failures.; Bankruptcy.; elektronické knihy; electronic books